Hubungan Antara Dukungan Sosial Orangtua dan Self Efficacy Dengan Kecemasan Dalam Menghadapi Dunia Kerja Pada Mahasiswa Semester Akhir Fakultas Psikologi Universitas Persada Indonesia YAI - Adi Muhammad Kasyfillah; Tanti Susilarini (Universitas Persada Indonesia YAI, 2021)
This study aims to determine the relationship between parental social support and self-efficacy with anxiety indealing with the world of work in final semester students of the psychology faculty of Universitas Persada IndonesiaYAI. The sampling technique used was convenience sampling with a population of 182 students and a researchsample of 107 students. The data collection technique uses three scales, namely the anxiety scale in dealing with theworld of work, parental social support, and self-efficacy. The results of the first bivariate correlation analysisbetween parental social support and anxiety in dealing with the world of work obtained a correlation coefficient (r)of -0.344 with p = 0.000 <0.05. So Ha1 which reads